Tourists' satisfaction on Kilim River mangrove forest ecotourism services - Ayob, Mohammad Zaki; Mohd Saman, Fatimah; Hussin, Zaliha; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Ecotourism is a revenue generator for many countries, especially those endowed with natural attractions. In order to sustain industry growth, its players are looking for essential factors contributing towards tourists’ satisfaction. This paper presents findings of a micro study on Langkawi mangrove forest ecotourism site along the Kilim River estuary. Four theoretical models were constructed and analyzed using Structural Equations Modeling (SEM). The Baseline Comparisons, Parsimony Adjusted Measures, and the RMSEA were used to evaluate good model fit and Model 3 was found to fulfill that fit. The overall tourist satisfaction index was found to be 79.1 of a possible 100 points. Significant contributing factors towards tourists’ satisfaction consist of marketing practices (42.1 percent), business ethics (23.9 percent), environmental management (14.5 percent), and business management/operational systems (7.8 percent).